Design of geosynthetic-reinforced slopes in cohesive backfills - Abd, Akram H.; Utili, Stefano (Geotextiles and geomembranes, 2017)
Currently, geosynthetic reinforcements for slopes are calculated assuming the ground strength to be purely frictional, i.e. without any cohesion. However, accounting for the presence of even a modest amount of cohesion could allow using locally available cohesive soils as backfills to a greater extent and less overall reinforcement. But cohesive soils are subject to the formation of cracks that tend to reduce slope stability so their presence has to be accounted for in the design of the slope reinforcement. In the paper, limit analysis was employed to derive a semi-analytical method for uniform c−ϕ slopes that provides the amount of reinforcement needed as a function of ground cohesion, tensile strength, angle of shearing resistance and of the slope inclination. Both climate induced cracks as well as cracks that form as part of the slope collapse mechanism are accounted for. Design charts providing the value of the required reinforcement strength and embedment length are plotted for both uniform and linearly increasing reinforcement distributions. From the results, it emerges that accounting for the presence of cohesion allows significant savings on the reinforcement to be made, and that cracks are often significantly detrimental to slope stability so they cannot be overlooked in the design calculations.